K2-99: a subgiant hosting a transiting warm Jupiter in an eccentric orbit and a long-period companion - Smith, Alexis M. S.; Wolthoff, Vera (Monthly notices of the Royal Astronomical Society, 2017)
We report the discovery from K2 of a transiting planet in an 18.25-d, eccentric (0.19 ± 0.04) orbit around K2-99, an 11th magnitude subgiant in Virgo. We confirm the planetary nature of the companion with radial velocities, and determine that the star is a metal-rich ([Fe/H] = 0.20 ± 0.05) subgiant, with mass $ $1.60^{+0.14}_{-0.10}$ $ M⊙ and radius 3.1 ± 0.1 R⊙. The planet has a mass of 0.97 ± 0.09 MJup and a radius 1.29 ± 0.05 RJup. A measured systemic radial acceleration of −2.12 ± 0.04 ms−1 d−1 offers compelling evidence for the existence of a third body in the system, perhaps a brown dwarf orbiting with a period of several hundred days.
Published: 30 September 2016
Gesehen am 12.10.2017